В поисках забвения : всемирная история наркотиков. 1500-2000 - Дейвенпорт-Хайнс Ричард (АСТ, 2004)
Экземпляры: аб. (2005) / Инвентарный номер: 48803 / Цена: / Сис.шифр: 51 / Авт.знак: Д 27 / ГРНТИ: 76.35.45 / ББК: 51.1(2)5